Design of a lightweight dual arm system for aerial manipulation. (April 2018) - Suarez, Alejandro; Jimenez-Cano, Antonio Enrique; Vega, Victor Manuel; Heredia, Guillermo; Rodriguez-Castaño, Angel; Ollero, Anibal
Highlights: Aerial manipulation allows physical contact tasks while flying. Design and development of lightweight (1.8 kg), human size dual arm manipulator. Dual arm manipulator integrated in multirotor platform. Derivation of the dynamics and controller of the dual arm aerial manipulator. Aerial manipulator design evaluated through experiments and outdoor flight tests. ABSTRACT: This paper presents the development and experimental validation of a low weight and inertia, human-size and highly dexterous dual arm system designed for aerial manipulation with multirotor platform. The arms, weighting 1.8 kg in total and with a maximum lift load per arm around 0.75 kg, provide five degrees of freedom (DOF) for end-effector positioning and wrist orientation. A customized aluminum frame structure supports the servo actuators, placing most part of the mass close to the shoulder structure in order to reduce the inertia. A double flange bearing mechanism in side-by-side configuration isolates the servos from impacts and radial/axial overloads, increasing robustness. This is important to prevent that the arms are damaged during physical interactions with the environment, as they should support the kinetic energy of the whole platform. The motivation in the development of a dual arm aerial manipulator is extending the range of applications and tasks that can be performed with respect to the single arm case, like grasping large objects or assembling. The paper covers the kinematic and dynamic modeling of the aerial robot, proposing a control scheme that deals with the technological limitations of the smart servo actuators. The performance of the arms and the interactions with the aerial platform are evaluated in test bench experiments. The proposed dual arm design is validated through outdoor flight tests with two commercial hexarotor platforms equipped with standard industrial autopilots. Graphical abstract: